2020
DOI: 10.2147/ott.s264614
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA MIR194-2HG Promotes Cell Proliferation and Metastasis via Regulation of miR-1207-5p/TCF19/Wnt/β-Catenin Signaling in Liver Cancer</p>

Abstract: LncRNAs play an important role in tumorigenesis and cancer progression in liver cancer. Although many lncRNAs have been reported, the role of MIR194-2HG and the underlying mechanism mediated by it are still largely unknown in HCC. This study aimed to investigate the biological role and mechanism of MIR194-2HG in liver cancer. Materials and Methods: The expression of MIR194-2HG was determined in liver cancer tissues and cells by RT-qPCR. The overall survival rate of MIR194-2HG was analyzed by Kaplan-Meier survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…31 Meanwhile, miR-1207-5p inhibits liver cancer proliferation and metastasis by regulating Wnt/b-Catenin signaling. 32 Moreover, miR-1207-5p can suppress gastric cancer progression via downregulating hTERT expression 33 and suppress colorectal cancer cell migration, invasion, and proliferation by targeting FMNL2. 34 These findings suggested that miR-1207-5p acts as a tumor inhibitor, suppressing malignant behavior.…”
Section: Discussionmentioning
confidence: 99%
“…31 Meanwhile, miR-1207-5p inhibits liver cancer proliferation and metastasis by regulating Wnt/b-Catenin signaling. 32 Moreover, miR-1207-5p can suppress gastric cancer progression via downregulating hTERT expression 33 and suppress colorectal cancer cell migration, invasion, and proliferation by targeting FMNL2. 34 These findings suggested that miR-1207-5p acts as a tumor inhibitor, suppressing malignant behavior.…”
Section: Discussionmentioning
confidence: 99%
“…e processes of carcinogenesis and immune regulation are significantly affected by the physiological effects of TCF19 activation. Since TCF19 is chronically activated, it is highly expressed in various solid tumors [12][13][14][15] and chronic inflammatory tissues [16][17][18]. e presence of highly expressed TCF19 has been found not only in invasive tumor tissues but also in malignant tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, lower levels of ncRNAs may also contribute to ceRNA sponge mechanisms, and even ceRNAs undergo marked rewiring between normal and pathological tissues 27 , 28 . Many previous studies have confirmed that lncRNAs play essential roles in the proliferation, metastasis, drug sensitivity, and progression of tumors 29 , 30 . Over the last few years, many studies have validated the ceRNA theory, as emerging evidence has verified that ceRNA crosstalk imbalance is associated with various diseases, especially cancers 26 28 .…”
Section: Introductionmentioning
confidence: 88%